Clock Gene Period in the Chagas Disease Vector Triatoma infestans (Hemiptera: Reduviidae) - Stroppa, Maria Mercedes (2018)
To contribute to a better understanding of the molecular bases of the circadian biological rhythms in Chagas disease vectors, in this work we identified functional domains in the sequences of the clock protein PERIOD (PER) in Rhodnius prolixus and Triatoma infestans and analyzed the expression of the PER gene at mRNA level in T. infestans. The PER protein sequences comparison among these species and those from other insects revealed that the most similar regions are the PAS domains and the most variable is the COOH-terminal. On the other hand, the per gene expression in nervous tissue of adult T. infestans varies with a daily canonical rhythm in groups of individuals maintained under photoperiod (light/dark, LD) and constant dark (DD), showing a significant peak of expression at sunset. The pattern of expression detected in LD persists under the DD condition. As expected, in the group maintained in constant light (LL), no daily increase was detected in per transcript level. Besides, the presence of per transcript in different tissues of adult individuals and in nervous tissue of nymphs evidenced activity of peripheral clocks in adults and activity of the central clock in nymphs of T. infestans.